Analysis Of The Effectiveness Of Communication Extension Palm Oil Plantation In Ptpn Iv Regional 1 Tanah Raja, Sei Rampah District Serdang Bedagai Regency - Frasiska, Cahaya; Depari, Nelfita Rizka S; Utami, Khairuna; Pulungan, Abraham Ismail (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
The effectiveness of communication plays a very important role in plantation farming activities, the need for information about oil palm cultivation aims to develop agricultural business results, production, and marketing cannot be separated from the role of communication that must be carried out by oil palm farmers on oil palm plantations PTPN IV regional I Tanah Raja plantation. This study aims to determine the effectiveness of communication on the Internal and External Characteristics of Oil Palm Farmers on Oil Palm Plantations PTPN IV regional I Tanah Raja plantation, Sei Rampah District, Serdang Bedagai Regency. Analysis of the Effectiveness of Oil Palm Farmer Communication was carried out using a survey method, sample selection with a purposive sampling method and a Likert scale analysis tool, and descriptive analysis. The effectiveness of group communicationThe score is 13.04, openness with a score of 11.04, Empathy has a score of 14.03, Attitude has a score of 13.05, positive attitude with a score of 14.04 and equality 11.02. Internal characteristics (education, age and gender) and external characteristics (intensity of counseling, accuracy of counseling channels and number of information sources) have a significant correlation with the effectiveness of group and interpersonal communication.